Integrating eye care into primary healthcare in Nigeria: Challenges of the primary healthcare workforce - Bet‐ini Nsikak Christian; Deborah Oluwaseun Shomuyiwa; Nsikak Godwin Christian; Ntiense Raphael Umoette (Wiley, 2024)
Abstract Visual impairment and blindness pose a significant and growing public health threat in Nigeria. Over 1.6 million Nigerians are visually impaired or blind, with more than 80% of these cases being preventable and treatable. The risk for ocular morbidities is expected to increase due to rapid population growth, an aging population, and the rising burden of noncommunicable diseases. Despite efforts to improve eye health services, universal eye health remains elusive, with 35% of Nigerians unable to access eye care in primary healthcare (PHC) facilities. Many Nigerians instead turn to traditional and alternative medicine for primary eye care (PEC), which can worsen their outcomes. This article highlights the potential of the country's PHC system to address these challenges, emphasizing the importance of PEC as an integral part of PHC. The article discusses the various challenges faced by PHC workers in delivering eye care services in Nigeria, focusing on financing, training, leadership, and policies for eye care. It also provides a set of comprehensive recommendations aimed at overcoming these challenges, including improved leadership and policy implementation, optimized financing, strengthened collaborations and partnerships, enhanced education and training, and effective human resource management systems. We emphasize the importance of holistic and strategic efforts to bolster the PHC workforce's capacity to provide universal eye healthcare in Nigeria, ultimately improving access to high‐quality eye care services for all.